How Large Changes in the Functioning Economy Effect Crime Rates in America: A National Examination of the Less Cash – Less Crime Paradigm - Hunt, Donald (2017)
The amount of cash in circulation appears to be decreasing the world over. With advances in payments technology, society is trending toward cashlessness. While the benefits are numerous, one particular advantage is its reducing effect on crime. Scholars on a global level continue to show that cash and crime are linked. Decreasing cash decreases crime and the reverse. However, this concept went untested in the US until recently. Taking advantage of legislation mandating that states replace welfare benefits checks with reloadable debit cards, Wright et al. explored the idea that this change reduced the amount of circulating cash and, subsequently, decreased predatory crimes. In this study, I build on that research by testing the same phenomenon but at a national level. I then add to these results by testing the cash and crime relationship on the states receiving the most benefits, the most urban states, and those with the highest rates of predatory crime controlling for relevant economic and social factors shown to influence crime. Findings for each of these analyses provide modest support for the hypothesis that reducing cash reduces street crime. I further test the notion that of drugs could be acting as the mechanism driving the need to commit crime for cash, but the data contained too much missingness and did not allow for a robust analysis. However, the general pattern of significant results imply that cash and street crime share a significant relationship. The results may also explain part of the American crime drop; not only by the decrease itself but perhaps also in the form of a crime shift. Policy implications advocate for continued advances in electronic payments, cooperation between government and private entities, and future explorations into new opportunities for crime in a digital age